All Work and No Play? Facilitating Serious Games and Gamified Applications in Participatory Urban Planning and Governance - Ampatzidou, Cristina (2018)
As games and gamified applications gain prominence in the academic debate on participatory practices, it is worth examining whether the application of such tools in the daily planning practice could be beneficial. This study identifies a research–practice gap in the current state of participatory urban planning practices in three European cities. Planners and policymakers acknowledge the benefits of employing such tools to illustrate complex urban issues, evoke social learning, and make participation more accessible. However, a series of impediments relating to planners’ inexperience with participatory methods, resource constraints, and sceptical adult audiences, limits the broader application of games and gamified applications within participatory urban planning practices. Games and gamified applications could become more widely employed within participatory planning processes when process facilitators become better educated and better able to judge the situations in which such tools could be implemented as part of the planning process, and if such applications are simple and useful, and if their development process is based on co-creation with the participating publics.